Facts and fabrications: experiences of law and legality among return migrants in Ukraine - Kubal, A (International Migration Institute, 2012)
How do return migrants reintegrate back into the society? This question has been explored by much academic scholarship interested in the migration and development nexus. This paper contributes to these debates, but focuses on the experiences of re-adaptation of return migrants in the legal sphere. It systematically addresses three interrelated questions. First, how do return migrants re-establish their relationship with the legal system upon arrival? Second, how do their experiences of return and re-adaptation, upon being exposed to different ways of understanding and relating to the law, contribute to their interpretations of legality, and influence their values and attitudes to law? Finally, how do return migrants’ responses to the law in the commonplace contribute to the production of legal knowledge? (cf. Yngvesson and Coutin 2006: 178; Riles 2006). The analysis is based on 99 in-depth interviews conducted in Ukraine with return migrants, family members of migrants and representatives of organizations that help return migrants reintegrate back into the society. The data has been gathered under the auspices of THEMIS project. Discussing migrants’ legal adaptations I pay particular attention to the logic of difference (Moore 1986) between how law and legality are being perceived ‘at home’ and abroad, and what this can tell us about 1) the safety and personal security of return migrants; 2) their relationships with the police, bureaucracy and local officials; and 3) their choice of career paths and business ventures in Ukraine. I employ the comparative lens on the role of law to grapple with the fabrications of some of socially constructed ‘myths’ about legality in Ukraine.